Хатній музей Івана Гончара як недержавний осередок вивчення локальної історії: “Україна та українці” - Патлань, Ю. (Науковi записки. Збiрник праць молодих вчених та аспiрантiв, 2009)
У статті розглянуто виникнення хатнього музею (1959–1993) Івана
Гончара (1911–1993) як результат особистісного зростання і національного
становлення скульптора та художника, склад документів меморіального
архіву І.М. Гончара, роль музею в фіксації усної, речової,
фотодокументальної локальної та регіональної історії України, створення
історико-етнографічного мистецького альбому «Україна та Українці» за
рукописами І.М. Гончара 1970-х–1990-х рр. В статье рассмотрены возникновение домашнего музея (1959–
1993) Ивана Гончара (1911–1993) как результат личностного роста и
национального становления скульптора и художника, состав документов
мемориального архива И.М. Гончара, роль музея в фиксации устной,
предметной, фотодокументальной локальной и региональной истории
Украины, создание историко-этнографического альбома-сборника “Украина
и Украинцы” по рукописям И.М. Гончара 1970-х–1990-х гг. The article deals with the creation of home museum of Ivan Honchar
(1911–1993), Ukrainian sculptor and artist, during 1959–1993. This process is
considered as being the result of artist’s personal development and national progress.
The documental structure of I.M. Honchar’s memorial archive is studied.
The role of the museum in the registration of Ukrainian local and regional history
in its verbal, material and photo-documental aspects is analyzed. On the base of I.M. Honchar’s manuscripts dated by 1970–1990-s, the work on creation of
“Ukraine and Ukrainians” historical and ethnographical art album is studied.